2016
DOI: 10.1002/jcla.21920
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum hs‐CRP Levels With the Presence of Obesity, Diabetes Mellitus, and Other Cardiovascular Risk Factors

Abstract: FBG, LDL-C, WC and gender are independently associated with serum hs-CRP concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
52
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 15 publications
7
52
0
1
Order By: Relevance
“…Besides, the present study found significant direct correlation between hs-CRP and total cholesterol, triglycerides, LDL and inverse correlation between hs-CRP and HDL. These findings are in accordance with conclusions of Ebrahimi et al [35] who studied hs-CRP levels, as a marker of inflammation, in a large sample of population without a history of cardiovascular or inflammatory disease and cancer, and to relate this to fasting blood glucose (FBG) and the presence of diabetes mellitus.…”
Section: Discussionsupporting
confidence: 92%
“…Besides, the present study found significant direct correlation between hs-CRP and total cholesterol, triglycerides, LDL and inverse correlation between hs-CRP and HDL. These findings are in accordance with conclusions of Ebrahimi et al [35] who studied hs-CRP levels, as a marker of inflammation, in a large sample of population without a history of cardiovascular or inflammatory disease and cancer, and to relate this to fasting blood glucose (FBG) and the presence of diabetes mellitus.…”
Section: Discussionsupporting
confidence: 92%
“…CRP is an inflammatory maker. Studies have been reported that CRP levels related insulin resistance with obesity . Risk of developing nonalcoholic fatty liver disease increased with a rising CRP level within the healthy cohort , and serum CRP levels decreased dramatically in obese subjects after bariatric surgery .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies were in agreement with our findings. For instance, Ebrahimi et al [25] performed a crosssectional study in order to evaluate the relationship between hs-CRP levels in presence of CVDs risk factors including DM, HTN and obesity. They recruited 7762 Iranian individuals with no previous history of cardiovascular events, malignancy or inflammatory disorders.…”
Section: Discussionmentioning
confidence: 99%